IMPLEMENTATION OF ISLAMIC PRODUCTION PRINCIPLES FOR CHILI FARMERS (CASE STUDY OF CHILI FARMERS IN SANGATTA UTARA) - Nur Hani’atul Latifah; Farah Dina Lutfiatunnisa; Sabrina Addini Maghfiroh; Varissa Amelia (Antis Publisher, 2024)
General Background: Agriculture in Indonesia, especially in the context of chili, plays a crucial role in the economy and food security. Spesific Background: This research focuses on the implementation of Islamic production principles among chili farmers in North Sangatta, East Kalimantan, who face challenges such as price fluctuations and climate change. Knowledge Gap: Limited studies have explored the integration of sharia values in agricultural practices, particularly in addressing sustainability and ethical production challenges. Aims: This study aims to understand how sharia values are applied in agricultural practices and their impact on productivity, sustainability, and social welfare among chili farmers. Results: Show that the application of the principles of tawhid, humanity, responsibility, benevolence, and justice not only increases productivity but also creates sustainability and ethics in production. These principles encourage farmers to not only focus on economic gain but also on social and environmental responsibility. Novelty: This study integrates Islamic economic theory with sustainable agricultural practices, demonstrating a harmonious framework between economic profit and social responsibility. Implications: The findings provide important insights into how the integration of Islamic production principles can support the welfare of farmers and society as a whole, while addressing global challenges such as climate change.